"Flip lid" type of lateral tibia plateau fracture with a meniscus radial tear: A case report. (August 2021) - Ho, Wei; Chih, Wei-Hsing; Yeh, Ming-Long; Lin, Shu-Fan; Su, Wei-Ren; Chiang, Chen-Hao
Abstract: Case: A 45-year-old woman sustained a unique lateral tibia plateau fracture pattern with a vertically rotated fragment composed of an intact articular surface and subchondral bone. During open reduction and internal fixation (ORIF), a full thickness radial tear of the lateral meniscus was found, which was repaired under direct visualization through arthrotomy. At final follow-up, the patient regained pain-free activity with good meniscus healing, as confirmed with a second-look arthroscopic examination. Conclusion: This case represents an undescribed fracture pattern that indicates an associated meniscus injury. A thorough evaluation, including Magnetic Resonance Imaging should be considered. One-stage ORIF followed with meniscus repair represents a good treatment option.